The development of an intrinsic programmed instruction text for use in systems performance and maintenance evaluation training - Martin, David ([s.n.], 1972)
The problem of this study is to develop and test an intrinsic programmed text for use in SPAME training. The text is constructed so as to satisfy the requirements of a prescribed set of behavioral objectives.